2019
DOI: 10.3390/atmos10090523
|View full text |Cite
|
Sign up to set email alerts
|

Relating Convection to GCM Grid-Scale Fields Using Cloud-Resolving Model Simulation of a Squall Line Observed during MC3E Field Experiment

Abstract: In this study, a WRF (Weather Research and Forecasting) model is used as a cloud-resolving model to simulate a squall line observed on 20 May 2011 in the Southern Great Plains (SGP) of the United States. The model output is then used to examine the relationships between convective precipitation and coarse-grained variables averaged over a range of subdomain sizes equivalent to various global climate model horizontal resolutions. The objective is to determine to what extent convection within the subdomains can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…We evaluate the representation of precipitation structure in cloud system resolving simulations of the 20 May 2011 squallline event during the Mid-Latitude Continental Convective Clouds Experiment (MC3E; Jensen et al 2016) in Oklahoma using radar observations. This case has been previously simulated in several previous studies (Tao et al 2013;Fan et al 2015;Marinescu et al 2016;Saleeby et al 2016;Tao et al 2016;Fan et al 2017;Fridlind et al 2017;Xue et al 2017;Cheng and Zhang 2019;Han et al 2019;Stanford et al 2019). Biases in simulated precipitation structure are then connected to differences in observed and simulated mesoscale circulations.…”
Section: Introductionmentioning
confidence: 72%
“…We evaluate the representation of precipitation structure in cloud system resolving simulations of the 20 May 2011 squallline event during the Mid-Latitude Continental Convective Clouds Experiment (MC3E; Jensen et al 2016) in Oklahoma using radar observations. This case has been previously simulated in several previous studies (Tao et al 2013;Fan et al 2015;Marinescu et al 2016;Saleeby et al 2016;Tao et al 2016;Fan et al 2017;Fridlind et al 2017;Xue et al 2017;Cheng and Zhang 2019;Han et al 2019;Stanford et al 2019). Biases in simulated precipitation structure are then connected to differences in observed and simulated mesoscale circulations.…”
Section: Introductionmentioning
confidence: 72%
“…In the mature stage, CAPE is often low, even though deep convection as well as moisture convergence can be intense (e.g., Fuchs‐Stone et al ., 2020). Moreover, adding Qadv to the instability closure allows for a better coupling of the convective parametrization to the dynamics, which is particularly important at high model resolutions (e.g., Cheng and Zhang, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the mature stage, CAPE is often low, even though deep convection as well as moisture convergence can be intense (e.g., Fuchs-Stone et al, 2020). Moreover, adding Q adv to the instability closure allows for a better coupling of the convective parametrization to the dynamics, which is particularly important at high model resolutions (e.g., Cheng and Zhang, 2019). We found that, over tropical Africa, the characteristics of convective precipitation agree best with GPM IMERG when Q adv is added to the instability closure, at both 9 and 4 km resolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation